A Real-time SAR Echo Simulator Based on FPGA and Parallel Computing - Xu Yinhui; Zeng Dazhi; Yan Tao; Xu Xiaoheng (Universitas Ahmad Dahlan, 2015)
This paper designs and implements a SAR (Synthetic Aperture Radar) real-time echo simulator based on multi-FPGA parallel computing. The one-dimensional frequency-domain Fourier transform algorithm is used in the simulator, and the echo signal model and the rapid calculation algorithm of impulse response function are introduced. The pipeline compute structure, multichannel parallel computing and procedure flow design are the key technologies of the simulator, which are also presented in details. And finally, the validity and correctness of the SAR echo simulator are verified through the imaging results of the point-array target and the nature scene target.